Dental health estimation for children age twelve and fifteen - Davidović Bojana; Ivanović Mirjana; Janković Svjetlana (Serbian Medical Society - Dental Section, Belgrade, 2012)
Introduction. The problem of chronic diseases such as caries is very complex because it appears very early in life, often during childhood. The number of involved people is growing as well as the number of affected teeth and surfaces that eventually lead to teeth loss. The aim of this study was to determine the dental status of adolescents age 12 and 15 in three municipalities in Bosnia, Foca, Cajnice and Kalinovik. Material and methods. The study included 506 school children both genders of six schools in three municipalities (Foca, Cajnice and Kalinovik). Teeth examination and criteria for diagnosis and coding were estimated based of criteria of the European Academy of Paediatric Dentistry (EAPD). To estimate dental health DMFT index [number of carious teeth (D), missing (M) and filled teeth (F)] and related indices (Person Caries Index, Teeth Caries Index, Average Caries Index and DMFT structure) were used. Results. Dental health status and caries prevalence were presented through the values of the Average Caries Index. The value of Average Caries Index for examined children was 6.17. Of all examined children 96.05% of them had at least one carious tooth. The average value of Teeth Caries Index was 23.04%. Conclusion. Dental health of the children in the examined region was characterized by high values of untreated carious teeth as well as the other components of DMFT index. Therefore, preventive measures and primary dental care must be implemented better among school children.